Pulau dan Identitas yang Ditinggalkan dalam Shimagomoru Karya Tami Sakiyama: Kritik Sastra Ekofeminisme - Ni Luh Putu Ari Sulatri; Silvia Damayanti (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
Tami Sakiyama in Shimagomoru criticises homogeneity, dominance, and centralisation influencing the thinking model and development strategy in Okinawa, causing violence toward society and the environment. This article examines the construction of discourse in Shimagomoru related to colonisation in Okinawa and its impact on the environment and universal bioethics through an ecofeminist literary criticism approach. The data in the study were collected through the literature review method and analysed through the descriptive analysis method. Results of this study showed that the islands abandoned by their inhabitants due to moving to the more advanced and modern main islands are the result of discrimination in modernisation and development in Okinawa. Colonisation, annexation, and assimilation created a single identity as Japanese for Okinawans, causing identity ambiguity.